Proceso para exportar orégano desde Sáchica Boyacá hacia el mercado de Alemania (2023)
Colombia has a great biodiversity in soils and climates, which is why we have a great advantage over other countries, which can lead us to be more competitive as a country in agricultural exports. Aromatic herbs are used worldwide for their medicinal, flavoring and seasoning properties.